Comparison of silver sulfadiazine and gentamicin for topical prophylaxis against burn wound sepsis. - Snelling, C. F. (1978)
Daily prophylactic application of either 1.0% silver sulfadiazine cream or 0.1% gentamicin cream was compared for effectiveness in preventing bacterial colonization of burn wounds and sepsis. Pseudomonas aeruginosa colonized the wounds of 37% of the 38 patients treated with silver sulfadiazine and 30% of the 33 patients treated with gentamicin; gentamicin-resistant P. aeruginosa colonized the wounds of 21% of the patients treated with gentamicin. Staphylococcus aureus colonization occurred in 55% of the patients treated with silver sulfadiazine, whereas colonization with Candida species occurred in 58% of the patients treated with gentamicin. Although gentamicin-resistant organisms caused no deaths their repeated appearance resulted in discontinuation of prophylaxiz with gentamicin cream. The next year P. aeruginosa strains resistant to gentamicin were isolated from burn wounds of only two patients who had not previously received parenteral therapy with gentamicin or tobramycin. Gentamicin cream should be reserved for treating patients with wounds infected by gentamicin-sensitive P. aeruginosa and those allergic to sulfa drugs. For most patients with burn wounds silver sulfadiazine is safe and effective as an antibacterial agent for topical prophylaxis.